2014
DOI: 10.1155/2014/148571
|View full text |Cite
|
Sign up to set email alerts
|

Bonding Effectiveness of Two Adhesive Luting Cements to Glass Fiber Posts: Pull-Out Evaluation of Three Different Post Surface Conditioning Methods

Abstract: The purpose of this study was to evaluate the bond strength at the post/resin-cement interface with 3 different surface treatments of glass fiber posts and with 2 different luting resin cements. Sixty glass fiber posts (RelyX Fiber Post) were randomly divided into 3 groups (n = 20) and were luted with a dual-polymerizing self-adhesive universal resin cement (RelyX Unicem) and with a dual-polymerizing resin cement (RelyX ARC). This was carried out in association with a dual-polymerizing adhesive (Scotchbond Mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
3

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 20 publications
(20 reference statements)
0
14
0
3
Order By: Relevance
“…These cements have appeared on the market with a proposal to simplify the adhesive bonding technique, with the use of cement in one step 14 , eliminating the demand for pretreatment of the tooth and the restoration 5 . Clearfil SA Cement and Multilink resin cements are considered simplified RC, since the Clearfil SA Cement is one-step selfadhesive cement and the Multilink is applied in an association with a self-etching adhesive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These cements have appeared on the market with a proposal to simplify the adhesive bonding technique, with the use of cement in one step 14 , eliminating the demand for pretreatment of the tooth and the restoration 5 . Clearfil SA Cement and Multilink resin cements are considered simplified RC, since the Clearfil SA Cement is one-step selfadhesive cement and the Multilink is applied in an association with a self-etching adhesive.…”
Section: Discussionmentioning
confidence: 99%
“…According to the treatment of dental tissue, the RC are classified: total-etch, self-etch or self-adhesive 2 . At present, all RC are based on the use of either an etch-and-rise or of a selfadhesive, however, application in stages technology is complex and considerably technology sensitive and thus may affect bonding efficiency 5 . The new self-adhesive, dual-polymerizing RC require no separate acid etching, priming or bonding resin applications to the prepared tooth surfaces before 6 .…”
mentioning
confidence: 99%
“…However, the large number of fiber posts used increase its cost and reduce its popularity [115]. Figure 3 shows a schematic drawing of preparation of specimens for pull-out test [70].…”
Section: Pull-out Testmentioning
confidence: 99%
“…The application of ascorbic acid is dependent on the increasing duration of exposure to the antioxidant [124]. Other examples are the use of ethanol [70,86], antioxidants such hesperidin, sodium ascorbate or rosmarinic acid [123]. Recently, a study of use of polidopamina at the post surface was found to be effective in improving the bond strength between resin cements and fiber posts without damaging the surface of the posts [57].…”
Section: Effect Of Surface Treatment Of Glass Fiber Posts On Bond Strmentioning
confidence: 99%
See 1 more Smart Citation